TEXTILE UPCYCLING FOR SUSTAINABLE FASHION: A CASE STUDY FROM NIFT SHILLONG - Das, Rimi; Gupta, Meenakshi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Northeast region of India, renowned for its abundant cultural variety, is home to a vivid drapery of traditional textiles essential to maintaining that diversity’s spirit. With their combination of generations-old indigenous designs, materials, and techniques, these textiles are a living tribute to the North East’s rich cultural inheritance. The North East has been a melting pot of varied tribes for generations, creating a cultural fusion where several tribal groups speak different languages, uphold their ancient rituals, maintain independent economies, and produce one-of-a-kind crafts and fabrics. In the past, when there were no other ways to verify a person’s goods and familial responsibilities, these textiles frequently functioned as identity cards. This paper will take you on a tour of the North East’s elaborately woven clothing and its way of draping the rectangular unstitched textile to make it look like apparel, many of which still exist today. The clothing, which is mostly made of unstitched fabric and is worn in various elegant, opulent, innovative, and different ways, gives rise to a distinct style and greatly influences how modern women dress. This paper will stress the importance of traditional textile apparel of the North East and explore how new traditions have been created by transferring artistic ideas through upcycling the present woven textile by using a zero-waste pattern method by the students of the fashion design department for sustaining the textile and styling to suit the tastes of the adopting lifestyle. The effort provided the students with a future business opportunity, alternative sources of cheaper materials, enriched creativity, and fun. The results revealed a noticeable change in the students’ approaches toward material usage and design methodology.